A Comparative evaluation of Non-descent vaginal hysterectomy versus total Abdominal hysterectomy: A hospital based case control study - BC, Durga; Sharma, Aseem; Mahaseth, Binod; Sharma, Nirmala (Journal of Nepalgunj Medical College, 2019)
Background: Hysterectomy is a common surgery performed by gynecologist worldwide. It can be done either by vaginal, abdominal or laparoscopic route. Non decent vaginal hysterectomy (NDVH) is less invasive, less time consuming and scar less surgery. The blood loss during surgery, intra-operative and post-operative complications are less in NDVH compare to TAH (total abdominal hysterectomy). Aim and objective: to compare the clinical outcome between NDVH and TAH. Method: A hospital based prospective study was done at Nepalgunj medical collage Kolhapur between March 2018–March 2019, 60 cases fulfilling selection criteria were selected, 30 cases underwent NDVH next 30 cases underwent TAH. Outcome is measured on the basis of operating time, blood loss during surgery, hospital stay and post-operative complications. Result: The most common indication for hysterectomy was fibroid uterus in both the groups (NDVH and TAH). The operating time, blood loss, hospital stay and post-operative complications were less in NDVH as compare to TAH. Conclusion: NDVH is a choice of surgery over TAH for freely mobile uterus with benign pathology and uterus size less than twelve weeks and without adenexal pathology.